South African censorship: the production & liberation of Waiting for the barbarians, by J. M Coetzee (Acta Scientiarum. Language and Culture, 2019)
During Apartheid, South African censorship became the main legal instrument for the control and cultural tutelage of society. Censors decided which literary works could be read. Thousands of books were withdrawn from circulation, but the censorship did not achieve total success in curtailing the circulation of ideas. One novel, in particular, was released despite being not only very political, but also representing events that were – as J. M Coetzee puts it – in the minds and hearts of people of conscience during Apartheid: torture and fake reports issued by the South African police. Through documental and critical analysis, this article aims to answer one question: why Waiting for the barbarians, novel by J. M Coetzee published in 1980, was never banned? We will bring information and reflections on how the use of literary strategies, a political strategy and the exercise of censorship by a peculiar censor were crucial for the system’s circumvention.